(untitled) (Journal of Social Sciences Review, 2022)
Self-objection and Facebook addiction have important effects on the mental health of every individual. However, very few studies have examined the correlation between depression symptoms, Facebook addiction, and self-objectification. The present study had two main objectives; first, to explore self-objectification and depression among students with Facebook addiction, and second to find out the family system, gender, and academic performance based on differences in study variables. Data was collected from 378 purposively selected Facebook-addicted students using The Bergen Facebook Addiction Scale (BFAS; Andreassen et al., 2012), Objectified Body Consciousness Scale (OBCS; McKinley & Hyd,e, 1996), and Zung Self-Rating Depression Scale (SDS; Zung, 1965). Study results showed that depression has a significant positive connection with self-objectification and Facebook addiction. Similarly, significant gender difference exists in self-objectification, depression, and Facebook addiction. The result indicated significant academic performance base differences exist on self-objectification and Facebook addiction, whereas differences are non-significant in nature on depression. The result also revealed that significant family system base differences on self-objectification and depression, and Facebook addiction.